Pharmacist Prescriber: Abroad Experiences and Possible Implementation in Slovenia - Štuhec, Matej (Anali PAZU, 2024)
The pharmacist prescriber represents a clinical pharmacist's most advanced role in drug prescription and therapy optimization. This collaborative practice initially emerged in the United Kingdom and the United States of America and later extended to other countries. Research findings indicate that this collaborative model yields positive outcomes, positively impacting clinical, humanistic, and economic outcomes while notably enhancing healthcare accessibility, particularly in the absence of family physicians. In Slovenia, pharmacist consultant settings have already been successfully integrated into the existing healthcare framework, laying a solid foundation for advancing collaboration in the form of prescribing pharmacists. This enhancement promises improved service accessibility, reduced physician workload, and heightened work quality. The reasons behind this collaborative approach in Slovenia are described in the paper.
Keywords: clinical pharmacy; prescribed by a pharmacist; it depends and independent prescribing medicines; evidence for prescribing pharmacists; Slovenia